The case of the vampire vacuum sweeper [compact disc, unabridged] - Erickson, John R., 1943- (Erickson, John R., 1943- Hank the Cowdog, 1997)
In his own modest way, Hank the Cowdog recounts how he barely escaped crazy Slim and his tail-eating vacuum sweeper and single-handedly saved the ranch from a huge catastrophe.